2021
DOI: 10.3390/app112210887
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Soil Particle Size on the Engineering Properties and Microstructure of a Red Clay

Abstract: Particle size exerts a significant influence on the mechanical behavior of soil. However, insufficient research has been carried out on red clay formations, which are widespread in some Chinese provinces. Here, using unconfined compressive strength (UCS) tests, wetting–drying (WD) tests, and low-temperature nitrogen adsorption tests, we examined the relationship between the particle size and a number of mechanical and microstructural characteristics of a red clay outcropping at a construction site in China. Ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…Among the main factors determining soil deformation is the particle size and the amount of fine fraction in soil, which are responsible for soil's mechanical properties and stability. Eventually, all cracks, layers, and large pores directly impact soil deformation and its mechanical properties under load (Wang et al 2021).…”
Section: Impact Of Soil Composition On Its Deformationmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the main factors determining soil deformation is the particle size and the amount of fine fraction in soil, which are responsible for soil's mechanical properties and stability. Eventually, all cracks, layers, and large pores directly impact soil deformation and its mechanical properties under load (Wang et al 2021).…”
Section: Impact Of Soil Composition On Its Deformationmentioning
confidence: 99%
“…2), while permeability decreases (Akayuli et al 2013;Reece 2021). Under applied load, the mechanism of soil failure changes from the splitting one to the shear one with the increasing soil particle size (Wang et al 2021). Generally, the content of grain size in soil is crucial for determining soil's stress-strain and strength characteristics.…”
Section: Impact Of Soil Composition On Its Deformationmentioning
confidence: 99%
See 1 more Smart Citation
“…The macroscopic physical and mechanical properties of the rock and soil as well as their specific engineering properties all depend on their microscopic structure (Zuo et al, 2016;NOWAMOOZ et al, 2016;Zhao et al, 2018;Zhou et al, 2021). However, most studies have focused on the micro-structure of the red clay, expansive soil, loess, and silty sand (ALDAOOD et al, 2014;Jiang et al, 2014;AHMED, 2015;Lin and Amy, 2015;Sun and Cui, 2018;Xiao et al, 2020;Wang et al, 2021), for instance. Some studies had also investigated the slope protection and the reinforcement of the CBS, the physical and the mechanical properties of the soil, and the micro-structure parameters (Hang et al, 2019;Huang and Zheng, 2021;Zhang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Qi et al researched the mechanical properties of red clay after indoor wet–dry cycles through triaxial consolidation drainage and direct shear tests [ 21 ]. Through the unconfined compressive strength (UCS), wetting–drying (WD), and low-temperature nitrogen adsorption tests, Wang et al found that the failure mechanism in the UCS test varies depending on the dry density [ 22 ]. Chen conducted shear tests on soil samples from different weather conditions and depths by embedding sensors inside the red clay slope and analyzing the characteristics and evolution process of slope failure [ 23 ].…”
Section: Introductionmentioning
confidence: 99%